Developing addition and subtraction of integers learning moduleusing ctl (contextual teaching and learning) approach Based on curriculum 2013 - Dyah Tri Wahyuningtyas; Raddin Nur Shinta; I Ketut Suastika (Pancaran Pendidikan, 2017)
This study aims todevelop alearning module foraddition and subtraction ofintegersusing Johnson’s CTL approach with some necessary adjustments. The development modelused inthis studywas designed based onPlompwhodivided itinto fivephases. However, the development design ofthis module only adopted four phases. The research instrumentpreparedin this studyconsistedof; (1) the questionnaire for the expertsandpractitioners, (2) the student questionnaire, (3) observationsheetsand questionnaires, (4) copies of the test. The subjectsof thisresearchwere thestudents of class IVBin SDN Kotalama 1. The finding showed that it met thecriteria forvalidity, practicality, andeffectiveness. The percentage of validity reached 90, 46%, while the percentageof the students who succeeded in the daily test[G1] was85 %, and the percentage ofstudent responseswas80%. In terms ofpracticality, the average score for validation resultwas 3, 6(high criteria) and the score from the observer’s questionnaire was 3, 2(high criteria). Since both resultsreachedhigh criteria,it could be concludedthat this developed modulewas practical.